Development an effective adsorptive treatment strategy for the removal of cadmium from textile wastewater by CuBi2O4@Fe3O4 nanocomposites - Buyuk, Muhammed Ali; Serbest, Hakan; Bozyigit, Gamze Dalgic; Bakirdere, Sezgin (TAYLOR & FRANCIS INC, 2025)
In this study, copper-bismuth oxide/iron oxide (CuBi2O4@Fe3O4) nanocomposites were prepared by microwave-assisted synthesis and used as adsorbents for the adsorptive removal of cadmium from textile wastewater. The pH/volume of buffer solution, mixing type/period and adsorbent dosage were optimized univariately to enhance the removal efficiency of the adsorbent and determined as 1.5 mL of pH 8.0 buffer solution, vortexing for 60s, and 30 mg of CuBi2O4@Fe3O4 nanocomposite material. Following the determination of the optimum parameters, equilibrium adsorption studies were performed at five different initial concentrations of cadmium within the range of 0.50 - 10 mg L-1 in textile wastewater. A matrix-matching calibration strategy was utilized for the accurate and precise quantification of cadmium in the wastewater matrix with a R-2 value of 0.9961. The percent removal efficiencies were calculated within the range of 77.2 - 81.5% for the adsorptive removal of cadmium ions from textile wastewater in the equilibrium adsorption experiments. Furthermore, the Langmuir, Freundlich, and Sips adsorption isotherm models were employed for modeling the equilibrium data, and the results showed that all the models fitted well with the experimental data with R-2 values higher than 0.99. The simple and efficient batch adsorption process developed was successfully utilized to remove cadmium ions from textile wastewater.
Keywords: Adsorption; cadmium; CuBi2O4@Fe3O4 nanocomposites; isotherm models; textile wastewater; HEAVY-METAL IONS; AQUEOUS-SOLUTION; LEAD; PRECONCENTRATION; NANOPARTICLES; SPECTROMETRY; ULTRASOUND; SEPARATION; SAMPLES; ACID; Engineering